Neighborhood Watch: What Your Utility Meter May Be Saying About You. Issue 6 (1st June 2013) - Spence, Shannon; Miller, Robert D.
Abstract : The smart grid promises efficient and effective use of gas, water, and electric resources via the deployment of smart meters and advanced metering infrastructure. Smart meters aim to provide real‐time usage information to central providers and to support autonomous control in order to facilitate desirable features such as demand response, demand forecasting, and flow monitoring. Because of the broadcast nature of the wireless channel, these messages are susceptible to eavesdropping.